The efforts of Kurdish women in narrating the Prophet's hadiths during the Mamluk era (648-923 AH / 1250-1517 AD) - Fatah, Prof.Dr.Fuzia Younis (Sulaimani Journal for Humanities, 2026)
This study aims to highlight the efforts of Kurdish women in narrating the Prophetic Hadith during the Mamluk era (648-923 AH/1250-1517 CE). Women made significant contributions to scholarly life, particularly in the Islamic sciences, with Hadith studies holding a prominent place. Hadith was considered one of the most important and noble sciences, and the second source of Islamic legislation. This era witnessed a great deal of interest among women in studying and transmitting Hadith, both in terms of narration and chain of transmission, in Egypt, the Levant, and the Hijaz. Kurdish women were among those who worked in the field of Hadith studies, rising to prominence and attaining the ranks of Musnadah (narrators of Hadith) and Muhaddithah (narrators of Hadith). Students traveled from various regions to them to learn Hadith, either by listening to them directly, reading to them, or receiving their permission to transmit. The study entitled “The Efforts of Kurdish Women in Narrating the Prophetic Hadith during the Mamluk Era (648-923 AH/1250-1517 AD)” was divided into an introduction and a conclusion, as well as two sections. The first section was devoted to discussing the efforts of Kurdish women in narrating the Prophetic Hadith during the Bahri Mamluk era (648-784 AH/1250-1382 AD), while the second section focused on the role of Kurdish women in narrating the Prophetic Hadith during the Burji (Circassian) Mamluk era (784-923 AH/1382-1517 AD).
Keywords: Kurdish women narration of the Prophetic Hadith during the Mamluk era